2008
DOI: 10.1039/b809291e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Gal4 DNA-binding domain is essential for activator mono-ubiquitylation and efficient promoter occupancy

Abstract: Recent analysis of a Gal4 mutant (Gap71) carrying three point mutations (S22D, K23Q and K25F) in its DNA-binding domain (DBD), has demonstrated that it cannot occupy GAL promoters efficiently in cells and that it is not mono-ubiquitylated, suggesting a functional link between this modification and stable DNA binding in cells. The mechanistic underpinning of this phenotype is that this protein is hypersensitive to a newly discovered activity of the proteasomal ATPases – their ability to actively dissociate tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…3b). Our data corroborate a previous report demonstrating that serine 22 is phosphorylated in vitro and that this phosphorylation event is important for subsequent monoubiquitination of Gal4 and formation of a stable Gal4-DNA complex (Ferdous et al, 2008). 1.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3b). Our data corroborate a previous report demonstrating that serine 22 is phosphorylated in vitro and that this phosphorylation event is important for subsequent monoubiquitination of Gal4 and formation of a stable Gal4-DNA complex (Ferdous et al, 2008). 1.…”
Section: Resultssupporting
confidence: 92%
“…Phosphorylation of Ser22 in the Gal4 DNA-binding domain has been demonstrated in vitro, and this modification has been shown to be essential for Gal4 monoubiquitylation. Ubiquitylation at lysine residue K23 in the DNA-binding domain is required to inhibit proteasomal destabilization of the activator-DNA complex (Ferdous et al, 2008). Interestingly, this study showed that phosphorylation of Ser22 does not require the Gal4 activation domain, while ubiquitylation requires both a DNA template and the activation domain.…”
Section: Introductionmentioning
confidence: 74%
“…When the Gal4-VP16⅐DNA complex was incubated with HeLa nuclear extract, an essentially quantitative monoubiquitylation of the activator was observed (32). Moreover, this event was found to be dependent on a preceding phosphorylation event at Ser 22 , located in the same domain (34). Remarkably, a DNA complex containing phosphorylated and monoubiquitylated Gal4-VP16 was completely resistant to disruption by the proteasomal ATPases (32).…”
Section: How Does Monoubiquitylation Stimulate Activated Gene Expressmentioning
confidence: 87%
“…For example, phosphorylation within the basic region can be either a positive (e.g. Gal4) (43) or negative (PRH/Hex) (31) influence. It has also been proposed that dimerization of STAT1 is regulated by phosphorylation (32,33), although others suggest that STATs exist as inactive dimers in the absence of phosphorylation (44,45).…”
Section: Discussionmentioning
confidence: 99%